UPAYA MENUTUP PELUANG KEPALA DAERAH KORUPSI KEMBALI DALAM MASA JABATAN YANG BERBEDA - Mahfudz Ali (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
Corruption is a crime against humanity. The impact is not only in the economic sector, but also destroys the entire structure of state life, even more devastatingly destroying the mentality of the nation's children. No state institution is immune from the virus of corruption. Regional heads who should be role models, according to the data from the Ministry of Home Affairs in 2019, 300 regional heads were involved in corruption. Among them, some had been imprisoned, then participated in the Regional Head General Election, and were elected, repeating corruption. This study answers the driving factors for why regional heads are corrupt again and finds efforts to minimize the recurrence of corruption by regional heads. With a case study of the facts of the trial in the court of a regional head who had been in prison. The result is large political financing with limited capital based on misguided intentions, the regional head even though he has been in prison will certainly repeat corruption. Opportunities that are used are buying and selling promotions for state civil servants, as well as commercializing projects by determining the winner who has deposited funds to the regional head. The effort to close this opportunity is to make a rule to include the Provincial Inspectorate in the promotion of echelon II and III positions. Meanwhile, to determine the winner of the project auction, namely to make regulations that require the local government to form an independent team financed by the regional government to oversee the auction and determine the winner of the auction. Maximizing the role of the Corruption Eradication Commission to tap the trusted people of the regional head who commercialize the authority of the regional head. Therefore, it is very urgent to establish a KPK in the Province